Review on Structural Performance of Composite Structures with Geopolymer Concrete and FRP Reinforcement - Chen, Yu; Zhu, Baoquan; Wei, Xinran (International Core Journal of Engineering, 2026)
Geopolymer concrete, utilizing industrial solid waste as raw materials, demonstrates low-carbon environmental friendliness and exceptional durability, making it an ideal alternative to traditional cement concrete. Fiber-reinforced plastic (FRP) bars possess advantages such as corrosion resistance, lightweight properties, and high strength, fundamentally addressing steel reinforcement corrosion issues. The composite structural system formed by these two materials shows broad application prospects in corrosive environments, underground engineering, and seismic-resistant structures. This article summarizes the interfacial bonding mechanisms between FRP bars and various concrete matrices, microscopic simulation methods, as well as the load-bearing and seismic performance of composite components. It identifies current research limitations in material stability, accelerator compatibility, specialized admixtures, interfacial mechanisms, and structural design. The study also outlines directions for multi-solid waste synergy, green activation techniques, interfacial modification, and engineering applications, providing references for future research and practical engineering in this field.